Pengaruh penambahan sari nanas terhadap karakteristik kimia dan sensori minuman teh cascara - Wiwik Endah Rahayu; Rita Purwasih; Dandy Hidayat (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
Cascara tea is a drink made from dry coffee skin from coffee beans stripping process result. The aim of this research is to study the effect of pineapple juice on chemical characteristics (Total Tated Acid (TAT), vitamin C, pH) and sensory test results of cascara tea drinks. The experimental design used was a complete randomized design with 3 treatment and 3 replications. The treatment used is T1: Control (without adding pineapple juice), T2: Add pineapple juice 25 %, T3: Add pineapple juice 35 %. The parameters observed are the chemical characteristics of TAT, vitamin C, and pH, also sensory test of color, taste, aroma, and overall appearance. The resulting data was analyzed by Variant Analysis (ANOVA) with a significance level of 5% and continue with the Duncan test. The results of experiments showed a addition of pineapple juice gave a significant value of TAT, vitamin C, and pH of cascara tea drinks (P <0.05). Sensory test results showed that pineapple juice addition gave significant value (P <0.05) for aroma, taste, and appearance overal and no significant effect (P> 0.05) for the color. 35 % addition of cascara tea liked by panelis.